Al-Qur - Rofi'i, Rofi'i; Dasuki, Akhmad; Hasan, Ahmad Fakhri (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2021)
This study aims to explore the use of the Quranic verses as the spiritual shield for the people of Hanjalipan village. This is a qualitative study with an anthropological approach. Data were acquired through observation, interviews, and documentary studies. It was conducted for 3 months, from February to May 2020. The data were analyzed with the living Quran method. The findings of this study lead to the conclusion that the Hanjalipan villagers believe in the Quran not only as the holy book but also as something that has spiritual power and can bring help when it is read. This belief encourages them to make certain verses as the self-shield from various calamities, diseases, and threats.Keywords :